EVALUASI DISCREPANCY PROGRAM SEKOLAH MINGGU BUDDHA SARIPUTRA : (Studi Evaluasi di Dk. Purwosari, Desa Sampetan, Kec. Gladagsari Kab. Boyolali Tahun 2022) - Mujiyanto Mujiyanto; Suranto Aw (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2023)
Buddhist Sunday School (SMB) is a non-formal teaching and learning activity that is carried out at the Vihara or Cetya every Sunday on a regular basis (PP.NO. 55 Article 44 paragraph 1 of 2007). Learning Objectives in SMB Activities are directed to instill faith (saddha) and also devotion in order to develop Buddhist beliefs on an ongoing basis. The purpose of this study was to determine the level of suitability/harmony between standards (standards or application/implementation) of the implementation of the SMB Sariputra program that had been determined in the program and the actual level of performance (performance/results of implementing the program). In addition to evaluating the SMB program in order to improve the quality of learning in accordance with the SMB National Curriculum standards. The method used in this study is qualitative evaluative research with the Discrepancy Evaluation Model approach by Malcolm M. Provus (1971) with 5 stages of implementation definition, installation, process, product, cost and benefit analysis). The research was conducted at the Buddhist Sunday School (SMB) Sariputra Dhamarsuci’s Monastery Purwosari, Sampetan Village, Gladagsari District, Boyolali Regency. Sources of information include: Head of SMB Sariputra, two SMB coaches, and two students' parents. Three gaps were found in the program implementation process but the program objectives had been achieved. Overall stages 1-5 in the Sariputra SMB parenting program have a good score of 69%, because they have carried out 4 of the 6 requirements for implementing SMB, namely (educational content or curriculum, number, qualifications of educators and educational staff, facilities and infrastructure, sources of financing, evaluation system, management and learning process). Researchers suggest continuing this program with improvements in accordance with established national standards. Abstrak Sekolah Minggu Buddha (SMB) merupakan kegiatan belajar mengajar nonformal yang dilaksanakan di Vihara atau Cetya setiap hari Minggu secara rutin (PP.NO. 55 Pasal 44 ayat 1 tahun 2007). Tujuan Pembelajaran pada Kegiatan SMB diarahkan untuk menanamkan keyakinan (saddha) dan juga bhakti dalam rangka mengembangkan keyakinan umat Buddha secara berkesinambungan. Tujuan penelitian ini untuk mengetahui tingkat kesesuaian/keselarasan antara baku (standar atau penerapan/pelaksanaan) penyelenggaraan program SMB Sariputra yang sudah ditentukan dalam program dengan tingkat kinerja (performance/hasil pelaksanakan program) sesungguhnya. Selain itu untuk mengevaluasi program SMB dalam rangka meningkatkan kualitas Pembelajaran yang sesuai dengan standar Nasional Kurikulum SMB. Metode yang digunakan dalam penelitian ini adalah penelitian evaluative kualitatif dengan pendekatan Discrepancy Evaluation Model oleh Malcolm M. Provus (1971) dengan 5 tahap pelaksanaan definition, instalation, process, product, cost and benefit analysis). Penelitian dilaksanakan di Sekolah Minggu Buddha (SMB) Sariputra Vihara Dhamarsuci Dk Purwosari Desa Sampetan Kecamatan Gladagsari Kabupaten Boyolali. Sumber informasi meliputi: Ketua SMB Sariputra, dua Pembina SMB, dan dua orang tua siswa. Ditemukan 3 kesenjangan dalam proses pelaksanaan program namun tujuan program telah tercapai. Keseluruhan tahap 1-5 di program parenting SMB Sariputra bernilai baik 69%, karena sudah menjalankan 4 dari 6 persyaratan penyelenggaraan SMB yaitu (isi pendidikan atau kurikulum, jumlah, kualifikasi pendidik, dan tenaga kependidikan, sarana dan prasarana, sumber pembiayaan, sistem evaluasi, manajemen dan proses pembelajaran). Peneliti menyarankan untuk melanjutkan program ini dengan perbaikan sesuai dengan standar Nasional yang ditetapkan.